The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1080/00380768.2014.984328
|View full text |Cite
|
Sign up to set email alerts
|

Cultivation effects on the carbon and nitrogen dynamics at depth in oasis farmlands of the Southern Tarim Basin, China

Abstract: The profile distribution of soil organic carbon (SOC) and total nitrogen (TN) are important indicators for predicting and simulating the effects of human activities on soil fertility and quality. However, most studies have focused on these changes in surface soil or the top 100 cm of short-term cultivated farmlands in arid regions. In the present study, farmlands cultivated for 0, 10, 15, 30, 80 and 100 years in the Cele oasis, at the southern margin of the Tarim Basin, were selected to examine cultivation eff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…Compared previous research in 2008 which showed that the average SOCC on the top 20 cm soil was only 2.89 g kg −1 (Si et al, ), our results showed a much higher amount (6.93 g kg −1 ). This number was also higher compared to other arid areas (e.g., <6 g kg −1 in the oasis of south Tarim basin, Xinjiang; Huang et al, ). The SOCC in the downstream Heihe River was lower than that in the middle reaches, likely due to differences in long‐term scarce precipitation and sparse vegetation.…”
Section: Discussionmentioning
confidence: 76%
“…Compared previous research in 2008 which showed that the average SOCC on the top 20 cm soil was only 2.89 g kg −1 (Si et al, ), our results showed a much higher amount (6.93 g kg −1 ). This number was also higher compared to other arid areas (e.g., <6 g kg −1 in the oasis of south Tarim basin, Xinjiang; Huang et al, ). The SOCC in the downstream Heihe River was lower than that in the middle reaches, likely due to differences in long‐term scarce precipitation and sparse vegetation.…”
Section: Discussionmentioning
confidence: 76%
“…In addition, other scholars have discovered that although nitrogen additions can increase vegetation productivity, litter inputs from aboveground leaves and underground roots have no significant positive feedback effects on nitrogen additions [46,60]. For Xinjiang, the increase in nitrogen may have been beneficial [47,61]. In regards to the WECC, the weighted average results show that the percentages of overloaded, critically overloaded and not overloaded counties and cities were 6%, 0% and 94%, respectively.…”
Section: Comparative Analysismentioning
confidence: 97%
“…N i represents the quantity of atmospheric pollutants. Different pollutants have different impacts on the environment, and the same pollutant has different impacts in different geographical environments [44][45][46][47]. Therefore, the weighted method to define the relative importance of each pollutant is more in line with the local actual situation.…”
Section: Assessment Of the Aecc • Short Board Effectmentioning
confidence: 99%